Reliability management of power systems with wind power generation and energy storage - Gao, Zhiyong (2013)
With increasing concerns of sustainable development of energy resources, many countries have planned to incorporate large percentages of renewable energy into their electrical power systems. Wind energy draws most attentions because it can be produced at acceptable cost with relatively mature technologies. Due to the intermittent and unpredictable nature of wind speed, power output from wind turbine generators (WTGs) is highly variable and uncontrollable. Many problems such as reliability and security issues will arise when existing power systems are integrated with high wind power penetration. New methods and techniques should be proposed to evaluate and solve these problems. This thesis focuses on investigating the impacts of integration of large amounts of wind power generation on power system reliability, and investigating optimal battery energy storage sizing techniques. The thesis focuses on operational reliability evaluation of power systems with wind energy and energy storage, and energy storage sizing techniques considering ramp rates of conventional generating units based on cost/worth analysis. Basic reliability evaluation techniques have also been introduced for easy understanding of power system reliability evaluation issue.